Implementasi Metode Hypnoteaching dalam Pembelajaran PAI - Miftakhurozaq Miftakhurozaq (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2018)
The learning process is the steps that pass with in development of students cognitive, affective, and psychomotor abilities. These three abilities must be possessed by students or learners. For achieving teachers must play an important role in the learning process. One of the role that a teacher has to go through these stages as a facilitator. One of education problems in Indonesia nowaday is the weakness of learning Process. In learning process, students are not supported enough to develope their skill of thinking. The learning process is only focus on asking students to study, but it is not focus on what they have to study. Hypnoteaching is one of the newest learning method development which is implemented by teachers at school. Hypnoteaching is a combination of five learning methods, they are quantum learning, accelerate learning, power teaching, Neuro-Linguistic Programming (NLP) and Hypnosis. Learning by Hypnoteaching method emphasizes student’s subconscious communication, which is implemented by several ways such as suggesting and imagining. By presenting this method, hopefully it can fix student’s problems at school. Therefore, the teachers are requested to be able to master the hypnoteaching method as the one of learning method at school in delivering the learning material optimally.